Cradle-to-Grave Emission Reduction for Easyhaler Dry Powder Inhaler Product Portfolio - Matleena Inget; Hanna Hisinger-Mölkänen; Myles Howard; Satu Lähelmä; Noora Paronen (Pulmonary Therapy, 2023)
Abstract Introduction There is increasing pressure to prefer propellant-free inhaler devices over pressurized metered-dose inhalers (pMDI) due to environmental considerations. In this work, we present results from three life cycle assessments (LCAs) on Easyhaler dry powder inhaler product portfolio and assess the changes in environmental impact and carbon footprint (CF) of the products over time. Methods Three cradle-to-grave LCAs were conducted in 2019, 2021, and 2023. The 2019 assessment covered four products while 2021 and 2023 assessments included all six products in the portfolio. LCA for the protective cover sometimes used with Easyhaler was conducted in 2023. In addition to CF, nine other environmental impact categories were assessed to ensure that no burden shifting occurs. Results During the study period, the non-weighted average CF of the Easyhaler decreased by 11.2%. For individual products, the decrease varied from 5.0 to 6.8% between the assessments. In the latest assessment, the average CF of Easyhaler was 547 gCO2e with a range of 452–617 gCO2e. The LCA of the protective cover was assessed for the first time in 2023 and had a CF of 66 gCO2e. Conclusions Our results show that the climate impact of pharmaceutical products can be reduced without making changes to the product itself. The CF of Easyhaler products is in agreement with the lower end of the CF range previously reported for dry powder inhalers. Climate impact from the protective cover was one-tenth compared to the climate impact from the product itself.